2015
DOI: 10.3390/ijms16047352
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Structure Prediction of Partial Length Protein Sequences of pcoA, pcoR and chrB Genes from Heavy Metal Resistant Bacteria from the Klip River, South Africa

Abstract: The Klip River has suffered from severe anthropogenic effects from industrial activities such as mining. Long-term exposure to heavy metal pollution has led to the development of heavy metal resistant strains of Pseudomonas sp. KR23, Lysinibacillus sp. KR25, and E. coli KR29. The objectives of this study were to characterize the genetics of copper and chromate resistance of the isolates. Copper and chromate resistance determinants were cloned and sequenced. Open reading frames (ORFs) related to the genes CopA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 56 publications
0
20
0
1
Order By: Relevance
“…More than one operon and gene are responsible for copper resistance in bacteria [8,12]. Although Chihomvu et al [11] detected pcoR gene in the E. coli isolates in an aquatic system of industrial pollutants, Dell' Amico et al [5] detected phenotypic resistance to copper in bacteria isolated from soil. However, he could not detect the presence of the pcoR gene using the PCR method and reported that there might be other genes responsible for resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than one operon and gene are responsible for copper resistance in bacteria [8,12]. Although Chihomvu et al [11] detected pcoR gene in the E. coli isolates in an aquatic system of industrial pollutants, Dell' Amico et al [5] detected phenotypic resistance to copper in bacteria isolated from soil. However, he could not detect the presence of the pcoR gene using the PCR method and reported that there might be other genes responsible for resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Then, deionized distilled water was added until the total volume became 25 µL. For thermal cycling of zntA, analyses were made according to Becerra-Castro et al [21], and for pcoR, the analyses were made according to Chihomvu et al [11]. As all the isolates were sensitive to mercury, the merA gene was not analyzed.…”
Section: Genotypic Determination Of Heavy Metal Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…In congruence, a study in Pseudomonas corrugata suggested that recG helicase played a crucial role in chromium tolerance by dismissing PAL lesions caused by Cr (VI)/Cr (III) [ 58 ]. The chrE gene encodes a rhodanese type enzyme [ 59 ]. Rhodanese protein subfamilies are suggested to be involved in different biological functions including cyanide detoxification, arsenic resistance and chromate responsive DNA-binding regulator.…”
Section: Discussionmentioning
confidence: 99%
“…The czcD gene involved in the regulation of the CZC zinc, cobalt, and cadmium efflux system was investigated by PCR according to Medardus et al ( 2014 ). The chromate resistance gene chrB was investigated as described by Chihomvu et al ( 2015 ) and Nies et al ( 1990 ).…”
Section: Methodsmentioning
confidence: 99%